Single-stage excision and sentinel lymph node biopsy in cutaneous melanoma in selected patients: a retrospective case–control study. Issue 6 (December 2017) - Giudice, Giuseppe; Robusto, Fabio; Vestita, Michelangelo; Annoscia, Paolo; Elia, Rossella; Nacchiero, Eleonora
Abstract : Sometimes, diagnostic excision of a primary melanoma would already necessitate skin grafting or transposition skin flaps, especially in areas with an esthetic or functional importance. The utility of sentinel lymph node biopsy (SLNB) after skin reconstruction is controversial. We carried out a single-institution retrospective case–control study. In patients with a wide primary lesion at high clinical–dermatoscopic suspicion for invasive melanoma in anatomical region in which a reconstruction with a skin graft or a flap is required, we proposed the performance of a confocal microscopy examination and an incisional biopsy of the primary lesion. If these diagnostic methodologies confirmed the suspicion of melanoma, lymphatic mapping was performed before the wide excision (WE) of the primary lesion, and WE and SLNB were performed during the same operative procedure. The database evaluation showed 496 patients who had undergone a previous complete local excision and a subsequent SLNB (two-stage group), whereas 61 patients underwent WE and SLNB during the same surgical time (one-stage group). Histological results of the excisional biopsy confirmed the diagnosis of melanoma in all patients of the one-stage group. The false-negative rate was lower in the one-stage group (5.5%) than in the two-stage group (16.7%). Patients of the two groups showed a similar recurrence-free and overall survival period even when corrected for clinic-demographical variables. The concomitant execution of SLNB and WE after confocal microscopy examination and incisional biopsy appears to be a safe and accurate procedure in patients with a wide primary melanoma that requires a skin flaps or a skin graft to cover the residual defect.